2019
DOI: 10.1007/s10340-019-01114-8
|View full text |Cite
|
Sign up to set email alerts
|

Can interactions among predators alter the natural regulation of an herbivore in a climate change scenario? The case of Tetranychus urticae and its predators in citrus

Abstract: Pest populations at climate change conditions can reach higher densities than forecasted according to its demographic parameters. Natural pest regulation provided by natural enemies depends on environmental conditions, is species-specific and is affected by interspecific interactions. Local extinctions may occur more frequently in a warmer future. Spider mite natural regulation can be seriously disrupted in a climate change scenario. Pest outbreaks may be increasingly more frequent in a warmer future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
23
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 84 publications
(96 reference statements)
5
23
2
1
Order By: Relevance
“…As expected, we found that T. urticae can develop faster on Cleopatra mandarin than on sour orange (Agut et al 2014 , 2016 ). The seasonal differences observed in our study have been repeatedly reported for this mite (Aucejo-Romero et al 2004 ; Urbaneja-Bernat et al 2019 ). Moreover, our results also provide evidence that E. stipulatus can directly feed on plants.…”
Section: Discussionsupporting
confidence: 88%
“…As expected, we found that T. urticae can develop faster on Cleopatra mandarin than on sour orange (Agut et al 2014 , 2016 ). The seasonal differences observed in our study have been repeatedly reported for this mite (Aucejo-Romero et al 2004 ; Urbaneja-Bernat et al 2019 ). Moreover, our results also provide evidence that E. stipulatus can directly feed on plants.…”
Section: Discussionsupporting
confidence: 88%
“…Probably because of the experimental setup used, where escapees could not seek shelter but instead died stuck in the glue, the highest impact of hot and dry conditions among phytoseiids was observed for the omnivore E. stipulatus. Theory would not predict, the highest impact of climate change on generalist instead of specialist predators, but this is what we were expecting based on previous semi-field assays (Urbaneja-Bernat et al, 2019). The survival of T. urticae in our experimental conditions was always above 60%, and it even reached 100% at 25ºC and 30% relative humidity (Figure 1).…”
Section: Discussioncontrasting
confidence: 48%
“…survival, oviposition, and predation) of T. urticae and its predators E. stipulatus, N. californicus and P. persimilis with and without provision of pollen as a supplementary food. The results of this work should help to explain the semi-field results observed (Urbaneja-Bernat et al, 2019) and provide evidence of whether pollen supply could be a tactic allowing the conservation of these natural enemies in a rapidly approaching warmer future.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Through convergent evolution, mites and thrips evolved stylets to facilitate feeding from mesophyll or epidermal cells (Bensoussan et al, 2016; Rioja et al, 2017; Wu et al, 2018). Despite large crops losses (Agut et al, 2018; Steenbergen et al, 2018) that are expected to become more severe with global warming (Ximenez-Embún et al, 2017; Urbaneja-Bernat et al, 2019), the interactions between mites/thrips and their host plants have been understudied. Hence, understanding how plants defend themselves against these pests is essential for developing crop protection strategies.…”
mentioning
confidence: 99%